How social support influences learned helplessness in lung cancer patients: the chain mediation role of individual resilience and self-efficacy - Huang, Jingui; Shi, Yumei; Chen, Yuemei; Tang, Ling; Zhang, Zhaoli (Frontiers in Psychology, 2024)
Background: Social support, which is a crucial external resource for cancer patients, was demonstrated to be a positive predictor of learned helplessness (LH). But it is far from clear whether and how social support decreases the LH in cancer patients. The purpose of present study is to detect the association between social support and LH and the role of individual resilience and self-efficacy in mediating this relationship.: The convenience sampling method was utilized. From August 2022 to February 2024, a total of 537 lung cancer patients (Mage=60.25years, SDage=9.85years) from five tertiary hospitals in one municipalities (Chongqing), and two provinces (Sichuan and Yunnan) were recruited, among which 389 were males and 148 were females. LH, social support, individual resilience, and self-efficacy were assessed by using standard scales. A structural equation model was constructed employing AMOS 23.0 to examine the interrelationships among social support, individual resilience, self-efficacy, and LH of lung cancer patients. Results: A total of 537 lung cancer patients were finally included. Social support, individual resilience, and self-efficacy were positively related to LH (r=-0.299 -0.451, p<0.01). The mediation model revealed that the direct effect of social support on LH was significant (β=-0.407, p<0.001). Besides, social support could also affect LH through three pathways: (1) the mediating effect of individual resilience (β=-0.075, p<0.001); (2) the mediating effect of self-efficacy (β=-0.060, p<0.05); (3) the chain mediating effect of individual resilience and self-efficacy (β=-0.011, p<0.05).The results indicate that social support alleviates lung cancer patients' LH, and that individual resilience and self-efficacy mediate the correlation between social support and LH. Besides providing adequate social support, intervention strategies built on individual resilience and self-efficacy should be applied to reduce LH in lung cancer patients.